The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1042/bj20041090
|View full text |Cite
|
Sign up to set email alerts
|

The septin Sept5/CDCrel-1 competes with α-SNAP for binding to the SNARE complex

Abstract: SNARE (soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor) proteins are supposed to mediate the docking and/or fusion of the vesicle with the plasma membrane. However, it is not clearly understood how this process is regulated. In a search for potential SNARE regulators, we recently identified septin 5 (Sept5) as a novel SNARE interacting protein.Septins were first identified as filamentous proteins required for cytokinesis in yeast. Several septins have now been identified in mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 50 publications
5
86
2
5
Order By: Relevance
“…78 Functionally, it has also been found that septin 5 binds to presynaptic SNARE complex proteins and inhibits exocytosis. 79,80 Indeed, many septins have been shown to have synaptic-associated binding partners which have been previously implicated in schizophrenia, for example syntaxin, complexin II and the microtubule-associated protein. [78][79][80] Septin 5 (also known as CDCrel-1 and Peanut-like 1) appears particularly interesting as it has been previously found to colocalize with GABAergic vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 Functionally, it has also been found that septin 5 binds to presynaptic SNARE complex proteins and inhibits exocytosis. 79,80 Indeed, many septins have been shown to have synaptic-associated binding partners which have been previously implicated in schizophrenia, for example syntaxin, complexin II and the microtubule-associated protein. [78][79][80] Septin 5 (also known as CDCrel-1 and Peanut-like 1) appears particularly interesting as it has been previously found to colocalize with GABAergic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 Indeed, many septins have been shown to have synaptic-associated binding partners which have been previously implicated in schizophrenia, for example syntaxin, complexin II and the microtubule-associated protein. [78][79][80] Septin 5 (also known as CDCrel-1 and Peanut-like 1) appears particularly interesting as it has been previously found to colocalize with GABAergic vesicles. 81 In a study investigating the distribution of septin 5 in the adult human brain, differential centrifugation revealed it to associate predominantly with neurons and to co-purify with SNAP-25 and synaptophysin marked synaptosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of expression and upregulation of septin 5 (SEPT5) is of particular interest, because septins play important roles in directing polarized addition of membrane (Beites et al, 2005), suggesting that septin proteins may play a crucial role in myelination. Transmembrane protein 10 (TMEM10) is a mostly uncharacterized protein that is highly enriched in white matter and whose gene is upregulated 24-fold during OL differentiation (Table 1), making it a novel candidate CNS myelin protein.…”
Section: Analysis Of Genes Most Highly Expressed By Ols or Induced Dumentioning
confidence: 99%
“…Among the many other cellular actin interacting partners, septins represent a group of small GTPases known to polymerize into oligomeric protein complexes and filaments (Surka et al 2002) that regulate cytokinesis, vesicle transport, and intracellular compartmentalization in a wide range of organisms (Beites et al 2005;Estey et al 2011). A member of the septin family, SEPT9, was initially identified as being recruited together with actin to the entry site of InlB-coated beads in LoVo cells (Pizarro-…”
Section: The Clathrin-mediated Endocytosis Machinery Is Involved In Tmentioning
confidence: 99%